2020
DOI: 10.29245/2572.942x/2020/3.1269
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Iglon5 Syndrome: What We Know So Far? A Non-Systematic Review

Abstract: The objective of this review is to provide an overview of the current knowledge of Anti-IgLON5 syndrome. The IgLON proteins are a family of cell adhesion molecules and the presence of antibodies against IgLON5 is crucial for the Anti-IgLON5 Syndrome diagnosis. This syndrome has an expanded clinical spectrum that involves prominent sleep disorder, progressive bulbar dysfunction, gait instability with abnormal eye movements reminiscent, and cognitive deterioration sometimes associated with chorea. The main neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Progressive Supranuclear Palsy (PSP) and Corticobasal Syndrome (CBS), could indicate that anti-IgLON5 is a novel tauopathy ( 17 ). Neuropathological investigations have shown that hyperphosphorylated tau has a propensity to gather in structures located in the basal part of the brain, including the hypothalamus, the tegmentum and periaqueductal gray matter ( 5 ). The correlation between the amount of aggregates and symptom severity needs to be investigated further.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Progressive Supranuclear Palsy (PSP) and Corticobasal Syndrome (CBS), could indicate that anti-IgLON5 is a novel tauopathy ( 17 ). Neuropathological investigations have shown that hyperphosphorylated tau has a propensity to gather in structures located in the basal part of the brain, including the hypothalamus, the tegmentum and periaqueductal gray matter ( 5 ). The correlation between the amount of aggregates and symptom severity needs to be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…IgLON genes can also regulate the level of renal perfusion due to glomerular afferent and efferent innervation and IgG anti-IgLON5 reactivity against renal glomeruli ( 3 , 4 ). The molecular structure of the IgLON5 protein can induce the production of specific antibodies in some cases, whose presence is crucial for anti-IgLON5 disease diagnosis, occurring with nonspecific symptoms like breathlessness during sleep, cognitive deterioration, gait disturbance and dysregulation of autonomic central nervous system (CNS) activity ( 5 ). The first cases of patients presenting i.a.…”
Section: Introduction – Iglon-5 - Physiological Role Pathogenetic Mec...mentioning
confidence: 99%
See 2 more Smart Citations